Blends of cassava starch with banana flours as raw materials for gluten-free biscuits - Leonel, Magali [UNESP] (2021)
The growth in demand for gluten-free products linked mainly to health aspects has led to an increased interest in the production of mixed flours for use in bakery products. This work aimed to evaluate the use of different mixtures of cassava starch with banana flour, obtained from the pulp and peel of green fruits, for the production of gluten-free biscuits. In the preparation of the biscuits, seven mixtures were prepared with varying percentages of cassava starch, banana pulp flour and banana peel flour. A formulation with wheat flour was used as a control. Wheat flour, cassava starch and banana flours were analyzed for chemical composition. The results showed that the banana peel flour stood out for its higher levels of proteins, fibres, lipids, ash, total phenols, total flavonoids and antioxidant activity which make this flour effective as a functional additive. However, the results of physical and sensory characteristics of the biscuits showed that the variation in the percentage of banana peel flour led to greater changes in the quality attributes of the biscuits, so the percentage of inclusion should be limited. Banana pulp flour (UBF) had high starch content, however, the biscuits produced with higher percentages of this flour and lower percentages of cassava starch showed lower propagation rates, greater hardness and less sensory acceptance, showing the importance of the starchy raw material in the physical properties of biscuits. Formulations containing cassava starch mixed with up to 15% banana flour (1:1, pulp and peel) are a good basis for making gluten-free biscuits.